(untitled) (Journal of the College of Basic Education, 2025)
The Arab Islamic civilization is one of the important civilizations in its creative achievements, as the Islamic religion was its foundation and an important source of inspiration in it. It was not far from artistic creations that were driven by ideas and beliefs. Thus, the Arab Muslim artist was able to transcend the prevailing creative concepts that surrounded him within the borders of the Arab nation or neighboring civilizations. This research consists of four chapters. The first c hapter represents the methodological framework, which dealt first with the research problem through the following question: Were the aesthetics of drawing achieved in the miniatures of the Baghdad School? And was the artist able to highlight these aesthetics in the miniatures of the Baghdad School of Painting. The second chapter included the theoretical framework of two sections, previous studies and their discussion, as well as extracting and discussing indicators from it to benefit from them in formulating the research tool, where the first section was: (The concept of miniature) and the second section: (The aesthetics of the formation of Islamic art).As for the third chapter, it included the research procedures, as the research community was determined and its sample of 3 works of art was chosen. The fourth chapter included the results and conclusions.